Aluminium-carbon fibre-reinforced polymer hybrid crash management system incorporating braided tubes. (2016) - Matheis, Ralf; Eckstein, Lutz
Based on axial crushing tests on generic braided carbon fibre-reinforced polymer (CFRP) tubes, a finite element (FE) simulation approach for these structures is developed. In a first step, an approach with individual material cards for different types of braiding structures is pursued and thus generalised to an approach, which can be conveniently adapted for different braiding parameters. Using this simulation approach, the braiding structure with the best specific energy absorption is determined and is consequently applied in the development of an aluminium-CFRP hybrid crash management system. This system incorporates a braided tube in a metallic crash box and is designed as a suitable substitute for the crash management system of a luxury class vehicle. Using FE approach, the structure is designed to absorb the kinetic energy in a low-speed collision (research council for automobile repair structural crash test) to prevent severe damage to the vehicle body, drive train, and chassis. Thus, the derived hybrid structure is built as physical prototype and tested under the boundary conditions of the reference test using a crash sled.